Numerical simulation of fully developed flow and heat transfer characteristics in a curved tube with pulsating pressure gradient - Back, Y.-R.; Lee, J.-H.; Kang, B.-H.; Oh, M.-D. (1994)
Characteristics of fluid flow and convective heat transfer of a pulsating flow in a curved tube have been investigated numerically. The tube wall is assumed to be maintained at a uniform temperature peripherally in a fully developed pulsating flow region. The temperature and flow distributions over a cross-section of a curved tube with the associated velocity field need to be studied in detail. This problem is of particular interest in the design of Stirling engine heat exchangers and in understanding the blood flow in the aorta. The time-dependent, elliptic governing equations are solved, employing finite volume technique. The periodic steady state results are obtained for various governing dimensionless parameters, such as Womersley number, pulsation amplitude ration, curvature ratio and Reynolds number. The numerical results indicate that the phase difference between the pressure gradient and averaged axial velocity increases gradually up to π/2 as Womersley number increases. However, this phase difference is almost independent of the amplitude ratio of pulsation. It is also found that the secondary flow patterns are strongly affected by the curvature ratio and Reynolds number. These, in turn, give a strong influence on the convective heat transfer from the pipe wall to the pulsating flow. The results obtained lead to a better understanding of the underlying physical process and also provide input that may be used to design the relevant system. The numerical approach is discussed in detail, and the aspects that must be included for an accurate simulation are discussed. ？ 1994, The Korean Society of Mechanical Engineers (KSME). All rights reserved.